2012
DOI: 10.5455/vetworld.2012.138-144
|View full text |Cite
|
Sign up to set email alerts
|

Clinical changes in sodium monoiodoacetate–induced stifle osteoarthritis model in dogs

Abstract: In six dogs, experimental model of osteoarthritis (OA) was reproduced by intraarticular injection of sodium monoiodoacetate (MIA) in left stifle joints. Contralateral joints served as control. The clinical status and some goniometric parameters were monitored before MIA introduction and at post injection days 30, 60 and 105. The results showed convincingly that the used experimental chemical OA model reproduced successfully the disease in canine stifle joints. The studied clinical indices correlated with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…In-context, MIA injection produced weight-bearing asymmetry in rats; this asymmetry was biphasic, possibly reflecting the initial inflammatory-driven phase of pain, followed by a second chronic phase that is connected to pathomorphological changes in the joint [50][51][52][53]. The observed low lameness score as the experiment proceeded in the current study could be due to the usage of a mild dose of MIA (25 mg), which did not induce severe lameness [37,54,55].…”
Section: Discussionmentioning
confidence: 60%
“…In-context, MIA injection produced weight-bearing asymmetry in rats; this asymmetry was biphasic, possibly reflecting the initial inflammatory-driven phase of pain, followed by a second chronic phase that is connected to pathomorphological changes in the joint [50][51][52][53]. The observed low lameness score as the experiment proceeded in the current study could be due to the usage of a mild dose of MIA (25 mg), which did not induce severe lameness [37,54,55].…”
Section: Discussionmentioning
confidence: 60%
“…Another possible explanation for visual scoring not being able to detect severe lameness over a longer period is that the dose of MIA used in this study was not high enough to induce more severe lameness. Data from horses and dogs [50,51] indicated that MIA should not be dosed on body weight. Therefore, the MIA-dose we administered to our pigs (20 mg in an 80 mg/mL solution) was based on a pilot study using three doses: 10 mg, 20 mg or 40 mg (Supplementary Material B, Tables S1–S2, Figure S4, Equation (S1)).…”
Section: Discussionmentioning
confidence: 99%
“… Model Large animals Key features Rodent equivalent? (Y/N) Naturally occurring arthritis Horse ( Coppelman et al, 2019 , Mariñas-Pardo et al, 2018 ; C. W. McIlwraith et al, 2012 ; Pujol et al, 2018 )Dog ( Alves et al, 2020 , Carter et al, 1999 , Malek et al, 2020 , Moreau et al, 2014 , Riley et al, 2016 )Pig ( Kreinest et al, 2016 , Macfadyen et al, 2019 )Monkey ( Carlson et al, 1994 , Rothschild et al, 1997 ) Behavior: Clinical signs of lamenessAppearance: Inflamed (for inflammatory arthritis)Pathology: anterior cruciate ligament deficiency; cartilage erosion; synovium thickening and fibrosis; osteophytes formation; subchondral bone thickening and neovascularisationMolecular: Proteoglycans and type II collagen loss in cartilage N, but occurs in transgenic animals ( Christensen et al, 2016 , Staines et al, 2017 ) Degeneration-focused models of arthritis Monosodium Iodoacetate (MIA) induced arthritis Pig ( Uilenreef et al, 2019 , Unger et al, 2018 )Dog ( Budsberg et al, 2019 , Goranov, 2012 , Pomonis et al, 2018 ) Behavior: Lameness; increased asymmetric weight bearing;Pathology: cartilage necrosis and discoloration; synovial membrane thickening; subchondral bone necrosisMolecular: Increased pro-inflammatory cytokine expression profile in synovium Y ( Harvey and Dickenson, 2009 , Udo et al, 2016 ) Osteochondral chip fragment model Horse ( Broeckx et al, 2019 , Frisbie et al, 1997 , Knych et al, 2017 ) Behavior: LamenessPathology: Subintimal hyperplasia and fibrosisMolecular: Inflammatory genes expression change in synovial fluid; structural genes (collagen and aggrecan) expression change in cartilage N Osteochondral/Chondral defect induced arthritis Horse ( Niemelä et al, 2019 , Salonius et al, 2019 ...…”
Section: Limitations Of Large Animal Researchmentioning
confidence: 99%